Religious harmony in India’s post-independence phase: a comparative study of the approach of Abul Hasan Ali Nadawi and Wahiduddin Khan - Khalil Ahmad, Siddiqi; Ali, Muhammad Mumtaz; Yousuf Azim, Siddiqi (IIUM Press, 2020)
In post-independent India, most of the Muslim intellectuals, scholars and organizations urged people to establish religious harmony in the country. However, Abū al-Hasan Ali Nadwi (1914-1999) and Waḥiduddin Khan (b.1925) emerged as the most influential Muslim scholars as they played a significant role in establishing religious harmony in the country. This research uses analytical and comparative methods to explain the approach of Nadwi and Khan concerning religious harmony. It critically investigates their approaches to determine the validity and relevance of their thoughts in contemporary India. The study found that Nadwi considers Muslims as significant contributors to Indian civilization and culture. Nadwi‟s suggestions do not only restore the courage among Muslims in India but imbue the essence of love, humanitarianism, peace and co-operation among all Indians. On the other hand, Khan‟s ideas are passive, unilateral and apologetic, and he considers Muslims as the cause of communal riots in the country. The study concludes that Nadwi‟s approach is more relevant and appropriate to contemporary Indian society to establish communal harmony. His approach appeared as courageous, especially for Muslim youth to contribute to the development of the country without compromising their faith and identity.